HUBUNGAN PENGETAHUAN IBU TENTANG ASUPANMAKAN DAN STATUS GIZI DENGAN FREKUENSI DIAREBALITA DI DESA BOLON, KECAMATAN COLOMADU,KABUPATEN KARANGANYAR - SALMA, FAUZYYAH; Dr.Mutalazimah, SKM., M.Kes., Dr.Mutalazimah, SKM., M.Kes; Dwi Sarbini, S. ST., M.Kes., Dwi Sarbini, S. ST., M.Kes (2016)
FAUZYYAH SALMA. J 300 120 046 RELATIONSHIP MOTHERS KNOWLEDGE ON FOOD INTAKE AND NUTRITIONAL STATUS OF CHILDREN UNDER FIVE YEAR WITH DIARRHEA FRECUENCY IN THE VILLAGE OF BOLON, COLOMADU, KARANGANYAR Background: Diarrheal disease is a health problem and the leading cause of death in infants. Mothers' knowledge of food intake and nutritional status of infants less causing diarrhea. Objectives: The study is to determine the relationship of mother's knowledge on food intake and nutritional status of children under five with diarrhea frequency in the village of Bolon, Colomadu, Karanganyar. Method: This research was conducted using observational analytic method with cross sectional approach. The subject of this research that mothers who have children aged 1-5 years by 39 mothers. Retrieving data using questionnaires knowledge of food intake and nutritional status of children under five year with diarrhea frequency. Data analysis using Rank spearman. Result: The level of mothers knowledge were divided into three groups, they are, good knowledge of 41%, 59% sufficient knowledge, and low knowledge 0%. Normal nutritional status of children is 74.4%, up 20.5%, and 5.1% overweight. The frequency of diarrhea were divided into two groups: ≤ 3 times 82.1% and 17.9% ≥ 3 times. The results analysis from relationship of mother's knowledge about food intake with the frequency of diarrhea (p = 0166). The results analysis of nutritional status relationship with the frequency of diarrhea (p = 0.434). Conclusion: There was no relationship mother's knowledge on the intake and nutritional status of children under five with diarrhea frequency in the village of Bolon, Colomadu, Karanganyar.